E-POSYANDU: WEB-BASED MOTHER AND CHILD POSYANDU APPLICATION USING THE CODEIGNITER FRAMEWORK - Wahyu Wijaya Widiyanto; Prita Devy Igiany; Arum Astika Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
POSYANDU (Integrated Service Post) is a monthly activity post to monitor the health status of pregnant women and toddlers (children under the age of five). This activity is carried out to monitor the growth and nutritional status of children under five on a regular basis and to understand the situation of pregnant women who are at risk so that preventive measures can be taken to prevent the death of pregnant women and malnourished children. However, in practice there are some difficulties such as searching for data and recording the same name in different formats. This study uses a qualitative method with a cross-sectional approach, where the aim of this research is to design and build a system that can manage Posyandu data in an integrated and well-computerized manner based on WEB cloud computing. The result of this study is a posyandu application consisting of immune data, vaccine data, child data, mother data, officer data, and posyandu data. The accuracy of the application implementation based on the blackbox method by posyandu officers who focus on the functionality side, especially on the input and output of the application by the officers, results of the application running according to the design requirements.